2022
DOI: 10.3390/atmos13030414
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Convectively Driven Flows in the Course of a Large Fire in Portugal: The Case of Pedrógão Grande

Abstract: The influence of a mesoscale convective system (MCS) in the evolution of two wildfires that started during the afternoon of 17 June 2017 in Pedrógão Grande, Central Portugal is discussed and analysed using weather radar data, weather stations, video images and fire spread analysis. As the MCS approached the region, its convectively driven flows started to influence the fires. The overturning flows were formed by two main limbs: one organised as front-to-rear deep layer inflows that propagated over the convecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 61 publications
5
25
0
1
Order By: Relevance
“…The interaction between the thunderstorm, organized as a mesoscale convective system (MCS), and the fire was extensively analyzed in Pinto et al (2022) using weather stations, satellite and radar observation data. The present work complements the previous reference, as the very unusual conditions that resulted from that interaction and produced the catastrophic fire during the late evening of that day are described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the thunderstorm, organized as a mesoscale convective system (MCS), and the fire was extensively analyzed in Pinto et al (2022) using weather stations, satellite and radar observation data. The present work complements the previous reference, as the very unusual conditions that resulted from that interaction and produced the catastrophic fire during the late evening of that day are described in detail.…”
Section: Introductionmentioning
confidence: 99%
“…(2017) showed that fire particles exhibit ρhv values lower than those associated to hydrometeors. In accordance with Pinto et al (2022), this study assumes that atmospheric volumes with ρhv ≤ 0.7 are mainly filled in by pyrometeors without significant condensation, whereas larger values correspond to atmospheric volumes with significant condensation/glaciation of pyrometeors.…”
Section: Radar and Surface Observationsmentioning
confidence: 72%
“…The fire complex of Pedrogão Grande, during 17-22 June 2017, was considered as the worst on record in Portugal due to the large burnt area and related fatalities, as described in Viegas et al (2017). The influence of a mesoscale convective system over the fires was analyzed in Pinto et al (2022) for an event of 17 June.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the magnitude of low-level reflectivity observed near the fire site is a good indicator of the overall intensity of strong convective processes caused by fire. A/PG radar was additionally used to verify if the suspected plume patterns were, in fact, originating from fire activity, based in the magnitude of the correlation coefficient that is processed in DP mode (Balakrishnan et al (1990), Pinto et al (2022)). Within the range of 100 km, the spatial resolution of the radar observations was 1 km or better.…”
Section: Methodsmentioning
confidence: 99%